Surgical management of idiopathic congenital talipes equinovarus by Carroll twin incision - Reddy, K. Vijaya Bhaskar; Lavudi, Narsimha (International Journal of Research in Orthopaedics, 2020)
Background: Surgery for congenital idiopathic clubfoot has a number of complications in the postoperative period such as delayed wound healing, gaping, infection, and recurrence of the deformity. The aim of this study is to evaluate the results of primary correction of clubfoot by modified Carroll’s double incision technique. Methods: It is a prospective interventional for a period of 2 years 5 months. 56 foot of which 21 pts have bilateral deformity and 14 pts with unilateral deformity. Patients of 3 months to 2 years age with idiopathic clubfoot, who did not respond to initial Ponseti casting; and were planned for Carroll double incision technique of surgery were included in this study. Results: In total 56 foot of which male are 23 and female children are 12 in number with male: female ratio of 1.9:1, showing male predominance, 21 pts have bilateral deformity and 14 pts with unilateral deformities. The mean change in radiographic parameters achieved by correction is as postoperative mean talocalcaneal index achieved was 42.60 (Normal range >40°). The postoperative mean anteroposterior talo-calcaneal angle was 26.20 (Normal range 300 to 550). The Postoperative mean lateral talo-calcaneal angle was 24.40 (normal 200 to 400). Final outcome is 81% is good, 14 fair and 5% has poor outcome. Conclusion: Exposure and release by Carroll’s twin incision is good, no tension in sutures, especially medical incision at the time of wound closure.